The Effectiveness of Gottman’s Systemic Cognitive Couple Therapy on Marital Conflicts, Communication Patterns, and Alexithymia in Couples with Marital Conflict - Salehi, Mohadeseh; Nikoo Abkenar, Bita; Rashidi, Tahereh (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The increasing prevalence of marital conflicts in contemporary society, the risk of separation, and its negative impact on the mental health of couples and their children is one of the most significant issues, sometimes affecting even three generations of a family. The effectiveness of Gottman’s Systemic Cognitive Couple Therapy on marital conflicts, communication patterns, and alexithymia in couples with marital conflict was examined. Methods and Materials: This study utilized an applied and quasi-experimental design with a pre-test, post-test, and follow-up, accompanied by a control group. The statistical population of this study included all couples who referred to counseling clinics in District 1 of Tehran from June to September 2023. Among them, 30 couples were selected through convenience sampling and randomly assigned to experimental and control groups. The interventions included seven sessions of Gottman’s Systemic Cognitive Couple Therapy (2008) administered to the experimental group. Data were collected using the Christensen and Sullaway (1984) Communication Patterns Questionnaire, the Bagby, Parker, and Taylor (1994) Alexithymia Scale, and the Barati and Sanai (1996) Marital Conflict Questionnaire. The data were analyzed using repeated measures ANOVA and SPSS-22 software. Findings: The results of data analysis indicated that systemic cognitive couple therapy was effective on marital conflicts (F=40.30, P<0.001), communication patterns (F=13.53, P<0.001), and alexithymia (F=3.59, P=0.036) in couples with marital conflict (P<0.01). Conclusion: It can be concluded that couple therapy can be utilized to improve marital conflicts, communication patterns, and alexithymia in couples experiencing marital conflict.